A Novel ELISA-Based Peptide Biosensor Assay for Screening ABL1 Activity in vitro: A Challenge for Precision Therapy in BCR-ABL1 and BCR-ABL1 Like Leukemias - Montecchini, Oksana; Braidotti, Stefania; Franca, Raffaella; Zudeh, Giulia; Boni, Christian; Sorio, Claudio; Toffoletti, Eleonora; Rabusin, Marco; Tommasini, Alberto; Decorti, Giuliana; Stocco, Gabriele (Frontiers in Pharmacology, 2021)
The pathogenic role of the overactivated ABL1 tyrosine kinase (TK) pathway is well recognized in some forms of BCR-ABL1 like acute lymphoblastic leukemia (ALL); TK inhibitors represent a useful therapeutic choice in these patients who respond poorly to conventional chemotherapy. Here we report a novel peptide biosensor (PABL)-ELISA assay to investigate ABL1 activity in four immortalized leukemic cell lines with different genetic background. The PABL sequence comprises an ABL1 tyrosine (Y) phosphorylation site and a targeting sequence that increases the specificity for ABL1; additional peptides (Y-site-mutated (PABL-F) and fully-phosphorylated (PPHOSPHO-ABL) biosensors) were included in the assay. After incubation with whole cell lysates, average PABL phosphorylation was significantly increased (basal versus PABL phosphorylation: 6.84 ± 1.46% versus 32.44 ± 3.25%, p-value < 0.0001, two-way ANOVA, Bonferroni post-test, percentages relative to PPHOSPHO-ABL in each cell line). Cell lines expressing ABL1-chimeric proteins (K562, ALL-SIL) presented the higher TK activity on PABL; a lower signal was instead observed for NALM6 and REH (p<0.001 and p<0.05 versus K562, respectively). Phosphorylation was ABL1-mediated, as demonstrated by the specific inhibition of imatinib (p<0.001 for K562, NALM6, ALL-SIL and p<0.01 for REH) in contrast to ruxolitinib (JAK2-inhibitor), and occurred on the ABL1 Y-site, as demonstrated by PABL-F whose phosphorylation was comparable to basal levels. In order to validate this novel PABL-ELISA assay on leukemic cells isolated from patient's bone marrow aspirates, preliminary analysis on blasts derived from an adult affected by chronic myeloid leukaemia (BCR-ABL1 positive) and a child affected by ALL (BCR-ABL1 negative) were performed. Phosphorylation of PABL was specifically inhibited after the incubation of BCR-ABL1 positive cell lysates with imatinib, but not with ruxolitinib. While requiring further optimization and validation in leukemic blasts to be of clinical interest, the PABL-based ELISA assay provides a novel in vitro tool for screening both the aberrant ABL1 activity in BCR-ABL1 like ALL leukemic cells and their potential response to TK inhibitors.